On the trail of the algorithm in the logistics sector: between organization and labor intermediation - Marco Guerini; Tommaso Maserati (Labour & Law Issues, 2025)
In the first part, the essay analyses the timing and modalities of digitalisation in the last-mile logistics sector, describing the forms that algorithmic management takes in the management of drivers' and porters' activities. These observations are then applied to the corporate structure typically found in the examined sector in Italy, i.e. the subcontracting chain, to identify the legal issues posed by this intersection to the interpreter. In this way, the authors seek to answer two questions: can the management of labour by means of algorithms by client companies be considered an instance of illicit labour brokerage, and what information tools are available to employees of contracting companies to “unveil” the algorithm and its user?